Neural responses in macaque prefrontal cortex are linked to strategic exploration - Jahn, Caroline I.; Grohn, Jan; Cuell, Steven; Emberton, Andrew; Bouret, Sebastien; Walton, Mark E.; Kolling, Nils; Sallet, Jérôme (PLOS Biology, 2023)
Humans have been shown to strategically explore; non-human primates are also thought to strategically explore, but do they use the same strategies and neural bases? This study reveals that monkeys strategically explore to improve future outcomes; such strategic exploration is linked to distinct signals in their frontal cortex.